Tren Terbaru Nanofiber Polikaprolakton Elektrospun: Perspektif Bibliometrik Lima Tahun dari 2019 hingga 2023 - Muhammad Rama Almafie; Rahma Dani; Idha Royani; Ida Sriyanti (Jurnal Penelitian Pendidikan IPA, 2025)
Nanofiber materials have emerged as a focal point of advanced research due to their exceptional properties. Polycaprolactone, a biodegradable and biocompatible polyester, has garnered particular interest for applications spanning tissue engineering, drug delivery, wound healing, and filtration. The electrospinning process facilitates precise control over PCL nanofiber morphology and functionality, enhancing its application potential. This investigation employs bibliometric analysis to elucidate global research trends in electrospun PCL nanofibers from 2019 to 2023. Utilizing the Scopus database, 255 relevant publications were identified through rigorous inclusion criteria, focusing on works that address PCL nanofibers, are published in English, and meet peer-reviewed standards. Quantitative tools, including VOSviewer and Harzing’s Publish or Perish, were utilized to analyze research trajectories, citation dynamics, and collaborative networks. Results underscore a predominant focus on biomedical applications, particularly drug delivery and tissue engineering. Geographically, research contributions are led by the Netherlands (28.63%), the United States (25.10%), and the United Kingdom (24.31%). The International Journal of Biological Macromolecules emerged as the most influential journal, contributing 22 articles (10%) and receiving 1,424 citations. Despite significant advancements, critical gaps remain, notably in scaling production processes and diversifying applications beyond the biomedical domain.